FUNDAMENTAL EFQM CONCEPTS AS THE BASIS OF THE UNIVERSITY QUALITY MANAGEMENT SYSTEM - Elena V. Khokhlova; Olga N. Fedisko; Galina V. Dub (Высшее образование в России)
The paper presents an original vision of the implementation process of the fundamental concepts of the European Foundation of Quality Management in terms of Russian universities. Identifying priority areas at different stages of its development, the University focuses on the fundamental concepts of the EFQM Excellence, which formed the basis of the philosophy of quality and inspired University to search for new areas of acquired knowledge and experience application.